УСТАНОВКА ДЛЯ КУЛЬТИВИРОВАНИЯ МОРСКИХ МИКРОВОДОРОСЛЕЙ - (:unkn) unknown (Севастополь: ЭКОСИ-Гидрофизика, 2005)
Предложена простая установка для интенсивного культивирования микроводорослей. При её разработке внимание уделено удобству в обслуживании и простоте изготовления. Учтена геометрия фотобиореактора. Показано, что для корректного сравнения экспериментальных результатов при использовании различных систем культивирования необходимо уделять особое внимание измерению фотоэнергетических характеристик.
Plant for cultivations of marina microalgae
Simple installation for intense cultivation of microalgae has been proposed. When developing the installation the following requirements were of primary importance: its serviceability and simplicity of its making as well as geometry of the photobioreactor. It has been pointed out, that for correct comparison of experimental results obtained by different authors with the use of different cultivation systems special attention must be paid to the measurement of photoenergetic characteristics.